Perspectives on evidentiality in Spanish explorations across genres - Figueras, Carolina; Cabedo Nebot, Adrián (Pragmatics & beyond new series (P&bns), 2018)
"Evidentiality in communication is better investigated in delimited and recognizable contexts where the multiple levels of meaning in interactional practices are manifested. Taking this viewpoint, the present volume explores the interrelations between evidentials and textual genre in Spanish. Adopting a discursive perspective, all of the chapters examine how the functional category of evidentiality is brought into discourse, which set of linguistic strategies makes explicit what counts as evidence in certain contexts and in certain textual genres, and what particular pragmatic meanings these mechanisms acquire, invoke and project onto the on-going discourse. In particular, this book is concerned with the relationship between evidential expressions and the pragmatic meaning(s) triggered by those expressions, and the role of genre in shaping the evidential meanings. The volume is addressed to both theoretically and empirically minded scholars in the disciplines of pragmatics, discourse analysis, sociolinguistics, communication studies, and psychology"--